The Language of Madness: Analyzing the Repetition and Obsession in The Short Story “The Tell-Tale Heart” through Discourse Analysis - Priscilla Abigail Giovanni Santoso; Ni Made Diana Erfiani Dewi; Yohanes Octavianus Lesu Awololon; Putu Chrisma Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study examines the discursive construction of madness in Edgar Allan Poe’s The Tell-Tale Heart through repetitive linguistic patterns that reflect psychological instability. By using a descriptive qualitative method within a Discourse Analysis framework, the data were analyzed through keyword frequency analysis, lexical repetition identification, and metafunctional interpretation of repeated keywords such as